2004
DOI: 10.1063/1.1640800
|View full text |Cite
|
Sign up to set email alerts
|

Light emission from a polymer transistor

Abstract: We report on light emission from a polymeric transistor that utilizes interdigitated source and drain electrodes with channel length of 5 μm in a bottom gate configuration based on a Si/SiO2 substrate. The polymer investigated is poly[9,9-di(ethylhexyl)fluorene] deposited by spin coating from chloroform solution to achieve an active layer thickness of 40 nm. Light emission occurs above drain source voltages of −60 V and the light intensity can be controlled by the gate voltage. Emission occurs close to the dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
64
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 16 publications
5
64
1
Order By: Relevance
“…As a consequence light emission occurs only at the interface between the semiconductor and the minority-carrier injecting electrode. [3][4][5][6][7][8] Only recently light emission from within the transistor channel was demonstrated in ambipolar OFETs (i.e., capable of transporting both holes and electrons). [9][10][11][12][13][14] In an ambipolar LEOFET when the gate is biased in between the source and drain potentials, holes and electrons are injected simultaneously at the opposite ends of the channel.…”
mentioning
confidence: 99%
“…As a consequence light emission occurs only at the interface between the semiconductor and the minority-carrier injecting electrode. [3][4][5][6][7][8] Only recently light emission from within the transistor channel was demonstrated in ambipolar OFETs (i.e., capable of transporting both holes and electrons). [9][10][11][12][13][14] In an ambipolar LEOFET when the gate is biased in between the source and drain potentials, holes and electrons are injected simultaneously at the opposite ends of the channel.…”
mentioning
confidence: 99%
“…Organic light emitting field-effect transistors [1][2][3] ͑LEFETs͒ are attracting interest due to a number of applications such as simplified pixels in flat panel displays, optoelectronic devices in communications, and potentially electrically driven lasers. A LEFET combines the emission properties of an organic light-emitting diode ͑OLED͒ with the switching properties of a transistor in a single device structure.…”
mentioning
confidence: 99%
“…In the same year, Omayada et al showed also a new single layer unipolar OLET with an EQE of almost 0.8%, made with a blend of 1wt%-rubrene doped tetraphenylpyrene (TPPy) (Omayada et al, 2005b). Other studies have been done using spin-coated or drop-casted polymers like polyphenylenevinylene, poly-fluorene or poly-arylenevinylene derivatives (Sakanoue et al, 2004;Ahles et al, 2004;Swensen et al, 2005a) as active layer. These experiments, besides showing a possible extension of the concept of unipolar OLET, demonstrated the feasibility of wet-technique fabrication process that could open up many possibilities of large-area and low cost devices.…”
Section: Unipolar Oletsmentioning
confidence: 99%